Pembatasan Volume Suara Azan Tinjauan Kaidah al-Ḍarar al-Asyad Yuzāl bi al-Ḍarar al-Akhaf: Limitations on the Volume of the Azan Sound in a Review of the Rules of al-Ḍarar al-Asyad Yuzāl bi al-Ḍarar al-Akhaf - Patuti, Asnawati; A. Hawariah; Asma, Asma (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research aims to find out what the law is for limiting the volume of the call to prayer and how to review the rules of al-ḍarar al-asyad yuzāl bi al-ḍarar al-akhaf in the matter of limiting the volume of the call to prayer. The problems the author raises are; How to review the rules of al-ḍarar al-asyad yuzāl bi al-ḍarar al-akhaf in the matter of limiting the volume of the call to prayer. This research methodology uses a qualitative descriptive (non-statistical) research type, which focuses on the study of manuscripts and texts, using normative and sociological research approaches. The research results found that limiting the volume of the call to prayer is permissible in reviewing the rules of al-ḍarar al-asyad yuzāl bi al-ḍarar al-akhaf. This is because limiting the volume of the loudspeakers will prevent larger ḍarar. However, the permissibility of limiting the volume of the call to prayer must be adjusted to the conditions of each region, the disturbance in question may be felt by residents in some areas, but not in others, so the application of restrictions on the volume of the call to prayer is returned to the policy owner in each region by considering the conditions people in the area. It is hoped that the implications of this research will become a reference, literature or consideration for the academic world, as well as positive reference material and information for the government, religious leaders and society in general.